About face. (Economist, 2004)
The article focuses on research on how the brain recognizes faces. Researchers are exploring how and where in the brain people recognise faces. This could be helpful to those who cannot recall them at all. To people with prosopagnosia, the instant someone leaves their sight the memory of that person's face is blank--or, at best, a palette of muddled features. Understanding the face-recall mechanism in the brain would be a big step towards understanding this odd disorder. The question is whether this crucial ability has its own private brain mechanism, or whether it is simply one aspect of a general ability to recognise individual members of a particular class of objects. A paper by Brad Duchaine and Ken Nakayama of Harvard University, which is to be published shortly in the Journal of Cognitive Neuroscience, uses face-blind volunteers to explore this question. While science has yet to pin down what it is that people with prosopagnosia are missing when they recall a blur instead of a face--and therefore what allows everybody else to be so good at recognising one another--it is making good progress towards that goal.